2009
DOI: 10.1590/s1676-06032009000300019
|View full text |Cite
|
Sign up to set email alerts
|

Non-flying mammals of Chapada Diamantina (Bahia, Brazil)

Abstract: Chapada Diamantina is located in central Bahia state, and has a large diversity of habitats, including important transitional areas, but has remained largely unstudied until now. In the present study we list the nonflying mammals of Chapada Diamantina National Park and surroundings. We captured only small non-volant mammals, medium and large mammals were assessed through indirect evidences (tracks and marks) and interviews. We recorded 58 species and 47 genera from seven Mammalian orders. Seven species are inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
5
15
0
2
Order By: Relevance
“…Á guas Emendadas Ecological Station, in the Federal District, with 11,000 ha, shows similar species richness (Marinho-Filho et al 1998) to Serra do Facã o region. Other studies found between 24 and 93 species for areas of different sizes and locations in the Brazilian cerrado (Mares et al 1989, Schneider 2000, Moreira et al 2008, Pereira & Geise 2009 (Table 2).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Á guas Emendadas Ecological Station, in the Federal District, with 11,000 ha, shows similar species richness (Marinho-Filho et al 1998) to Serra do Facã o region. Other studies found between 24 and 93 species for areas of different sizes and locations in the Brazilian cerrado (Mares et al 1989, Schneider 2000, Moreira et al 2008, Pereira & Geise 2009 (Table 2).…”
Section: Discussionmentioning
confidence: 81%
“…This pattern is expected for the cerrado biome (Marinho-Filho et al 2002). Considering studies in Protected Areas of cerrado and those that make use of pitfalls in addition to conventional traps, the richness of small non-flying mammals ranged from 19 to 29 species (Schneider 2000, Marinho-Filho et al 2002, Pereira & Geise 2009, Carmignotto & Aires 2011, Bonvicino et al 2012). This richness is similar (or even large) than our study, despite our larger sample effort ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…As for the mammals, most species inhabiting CRs are ordinarily found in other vegetation complexes in the Cerrado matrix such as the Cerrado sensu stricto (e.g., Pereira and Geise, 2009), but a few select taxa seem to be endemic or at least rarely recorded elsewhere. Mammal species possibly endemic of the CRs are usually restricted to one or a few mountain ranges of the same massif.…”
Section: Circumscription and Discussionmentioning
confidence: 99%
“…The only case of a mammal known exclusively from CRs is Olygoryzomys rupestris Weksler & Bonvicino, 2005, a sigmodont rodent that has been recorded so far only in widely isolated localities: Alto Paraíso, Goiás, Chapada dos Veadeiros, in Goiás state, and two scattered localities in the Chapada Diamantina, northern Espinhaço range, state of Bahia. So far this species has only been captured at high altitudes (1500m) either in CRs or on their limits with adjacent vegetation (Weksler and Bonvicino, 2005;Pereira and Geise, 2009). …”
Section: Circumscription and Discussionmentioning
confidence: 99%
“…1). In Brazil, the species has been recently reported in the states of Mato Grosso do Sul (Carmingnotto et al, 2014), São Paulo (Vivo et al, 2011), Tocantins (Di-Nizo et al, 2015, Pará , and Bahia (Pereira and Geise, 2009). Therefore, O. mattogrossae is found in the Brazilian Caatinga (Bahia, Alagoas, Pernambuco, Paraíba states) and Cerrado (Distrito Federal, São Paulo, Minas Gerais, Mato Grosso, Mato Grosso do Sul, Goiás, Tocantins, Bahia, and Maranhão states).…”
Section: Taxonomic Accountmentioning
confidence: 99%